A Critical-Historical Review of Program Evaluation and the Emerging Motif ‘Evaluation Science’ - William James Fear (Journal of MultiDisciplinary Evaluation)
Background: It is important to distinguish between evaluation as an inherent, automatic, affective process and Program Evaluation (Evaluation, with capitalised ‘E’) as an institution, and equally important to consider what a good understanding of evaluation tells us about Evaluation. Evaluation is an established social institution whose modern roots can be traced back to 16th century France. Since the early 1900s the institution has developed within and across a range of scientific disciplines with interests in perceived social problems and efforts to resolve the said problems. This can be demonstrated objectively by the number and scale of relevant publications within relevant disciplines. This, in turn, helps us understand more about Evaluation as an institution. Set in this context is the question of Evaluation Science: is this simply a fashionable institutional motif or is it a potential new era for Evaluation?